2018
DOI: 10.3390/catal8110542
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on Facet-Dependent Deposition of Metal Nanoparticles on Decahedral-Shaped Anatase Titania Photocatalyst Particles

Abstract: Facet-selective gold or platinum-nanoparticle deposition on decahedral-shaped anatase titania particles (DAPs) exposing {001} and {101} facets via photodeposition (PD) from metal-complex sources was reexamined using DAPs prepared with gas-phase reaction of titanium (IV) chloride and oxygen by quantitatively evaluating the area deposition density on {001} and {101} and comparing with the results of deposition from colloidal metal particles in the dark (CDD) or under photoirradiation (CDL). The observed facet se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…73 Therefore, we envisage that "gentle" surface modification methods like ALD may be leveraged for interfacial engineering of, for example, {001} facets on atomic level with high impact on photocatalytic activity. Importantly, in line with results of Mul et al 47 and Ohtani et al, 29 we found no evidence for inherently anisotropic charge transport in crystals with well-defined facets that would, rather independently from reactions occurring at the surface, drive photogenerated electrons preferentially to {101} facets and holes to {001} facets, as often suggested. [20][21][22][23][24][25][26][27] Is then the proposal to utilize well-defined crystals for construction of highly efficient photocatalysts with oxidation and reduction reactions occurring at different facets simply misguided?…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…73 Therefore, we envisage that "gentle" surface modification methods like ALD may be leveraged for interfacial engineering of, for example, {001} facets on atomic level with high impact on photocatalytic activity. Importantly, in line with results of Mul et al 47 and Ohtani et al, 29 we found no evidence for inherently anisotropic charge transport in crystals with well-defined facets that would, rather independently from reactions occurring at the surface, drive photogenerated electrons preferentially to {101} facets and holes to {001} facets, as often suggested. [20][21][22][23][24][25][26][27] Is then the proposal to utilize well-defined crystals for construction of highly efficient photocatalysts with oxidation and reduction reactions occurring at different facets simply misguided?…”
Section: Discussionsupporting
confidence: 92%
“…In this context, we point out that this reasoning is in line with the results of Mul et al on facet-selective deposition of Pt onto WO3 crystals who demonstrated that the facet-specific Pt photodeposition is caused by preferential facet-specific adsorption of the Pt precursor, 47 rather than by any intrinsic facet-selective separation of photogenerated charges during photodeposition. Similarly, in case of (non-fluorinated) anatase TiO2, Ohtani et al recently also highlighted the importance of surface charge and adsorption properties of different facets for facet-selectivity of metal photodeposition, 29 and found no conclusive evidence for any intrinsic facet-selective transport of photogenerated electrons and holes to {101} and {001} facets, respectively. The latter has been frequently suggested in the literature [20][21][22][23][24][25][26][27] and explained, for example, by anisotropic effective mass of electrons and holes in anatase, 26 or by different surface energetics of {101} and {001} facets resulting in electric potential difference (band bending) at their interface.…”
Section: A Photodeposition Of Pt On Well-defined Anatase Tio2 Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed that both the selective deposition of metal/oxides (e.g., [73]) and an appearance of reaction products on selective facets (e.g., [126]) do not unequivocally confirm whether that particular reaction happens on that facet. For example, Kobayashi et al has shown that the adsorption of noble metals depends on the surface charges and pH value of the reaction mixture [127].…”
Section: Faceted Titaniamentioning
confidence: 99%
“…Kobayashi et al have shown that adsorption of noble metals on DAP facets depends on the surface charges and pH value of the reaction mixture[91].Similar issue has been examined by Zielinska-Jurek et al where Pt NPs have been deposited on DAP by different methods…”
mentioning
confidence: 69%